Hubungan Antara Aktivitas Fisik dan Pola Makan Dengan Kejadian Obesitas pada Anak Sekolah Dasar SD Negeri 1 Setia Bakti Lampung Tengah Tahun 2024 - Agita, Ni Made Amelia Dewi; Karyus, Aila; Astuti, Dewi Woro (CV. Rayyan Dwi Bharata, 2025)
Child nutrition problems now involve malnutrition and obesity, both of which can be influenced by diet and physical activity. This study at SD Negeri 1 Setia Bakti, Central Lampung in 2024, aims to determine the relationship between physical activity and dietary patterns with obesity. Using a quantitative cross-sectional design, 100 respondents were selected via probability sampling. The analysis revealed that 52% had low physical activity, 38% had excessive dietary patterns, and 31% were obese. The chi-square test showed a significant relationship between physical activity (p-value=0.002) and dietary patterns (p-value=0.000) with obesity. Collaboration between schools and families is recommended to address these issues through education and awareness to promote healthier lifestyles for children.